Portugal and air transport in the early 21st century - Button, Kenneth (2013)
The Nature of air transport 1. Air transport is important • It is a big industry • It is vital to many industries and regions 2. It is multi-facited • Airlines • Airports • Air traffic control • Domestic and international 3. It is a network Industry • Portugal is part of Europe (legal fact) • Portugal is part of the world (globalization) 4. It is not wanted for its own sake • It “facilitates” and does not create 5. It has environmental implications • Noise • Greenhouse gas emissions